Synthesis of end-user research to inform future multipurpose prevention technologies in sub-Saharan Africa: a scoping review - Bhushan, Nivedita L.; Ridgeway, Kathleen; Luecke, Ellen H.; Palanee-Phillips, Thesla; Montgomery, Elizabeth T.; Minnis, Alexandra M. (Frontiers in Reproductive Health, 2023)
Introduction Women in sub-Saharan Africa (SSA) experience disproportionately high rates of HIV infection and unintended pregnancy compared to their age-matched counterparts in other regions of the world. Multipurpose prevention technologies (MPTs) that offer protection against HIV and unintended pregnancy in a single product stand to address these dual sexual and reproductive health needs simultaneously. The aim of this scoping review is to identify factors that are important for optimizing the likelihood of MPT adoption by end users in SSA. Methods Study inclusion criteria included MPT research (HIV and pregnancy prevention dual indication) published or presented in English from 2000 to 2022 and conducted in SSA amongst end-users (women aged 15–44), male partners, health care providers, and community stakeholders. References were identified by searching peer reviewed literature, grey literature, conference presentations (2015–2022), grant databases, and outreach to MPT subject matter experts. Of 115 references identified, 37 references met inclusion criteria and were extracted for analysis. A narrative synthesis approach was used to summarize findings within and across MPT products. Results Studies were identified from six countries in SSA and a substantial proportion included a South African (n = 27) and/or Kenyan (n = 16) study site. Most studies utilized a qualitative study design (n = 22) and evaluated MPT acceptability and preferences by presenting hypothetical products through images or a list of product attributes (n = 21). The vaginal ring (n = 20), oral tablet (n = 20), and injection (n = 15) were examined most frequently. Across studies, there was high acceptability and demand for an HIV and pregnancy prevention MPT. End users valued choice in prevention product type as well as discreetness and long-acting options. Provider counseling and community sensitization were reported as essential for future introduction of novel MPT delivery forms. Conclusion Recognizing the heterogeneity of women's preferences and changing reproductive and sexual health needs over the life course, choice is important in the delivery of pregnancy and HIV prevention products as well as amongst MPT products with distinct product profiles. End user research with active MPTs, vs. hypothetical or placebo MPTs, is necessary to advance understanding of end-user preferences and acceptability of future products.